Macromolecular Degradation Systems and Cardiovascular Aging. Issue 10 (13th May 2016) - Nakayama, Hiroyuki; Nishida, Kazuhiko; Otsu, Kinya
Abstract : Aging-related cardiovascular diseases are a rapidly increasing problem worldwide. Cardiac aging demonstrates progressive decline of diastolic dysfunction of ventricle and increase in ventricular and arterial stiffness accompanied by increased fibrosis stimulated by angiotensin II and proinflammatory cytokines. Reactive oxygen species and multiple signaling pathways on cellular senescence play major roles in the process. Aging is also associated with an alteration in steady state of macromolecular dynamics including a dysfunction of protein synthesis and degradation. Currently, impaired macromolecular degradation is considered to be closely related to enhanced inflammation and be involved in the process and mechanism of cardiac aging. Herein, we review the role and mechanisms of the degradation system of intracellular macromolecules in the process and pathophysiology of cardiovascular aging.